Performance Evaluation Of A Zero Head PicohydroTurbine-GeneratorSystem - Sumagayan, Moheddin; Estoperez, Noel (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
This paper presents the characterization of an existing three- bladed Gorlov helical turbine and a permanent synchronous DC generator. It also shows the design, assembly and performance evaluation of the zero head picohydro turbine-generator system using the aforementioned three-bladed Gorlov helical turbine and DC generator. A flume at the input/suction and a “water lens-inspired” shroud at the output/discharge were attached to the assembly as efficiency enhancements to the system. Free-flowing spring waters from Mimar’s Springway Resort was used as input to the system to generate electricity. Two different drive systems were used to evaluate the performance of the said system. The V-belt drive and chain-and-sprocket drive were used and tested separately. Results showed that there was no significant variation in power outputs using either of the two drive systems. The overall efficiency of this zero head picohydro turbine-generator system was 29%. The ZH PHTG system replication is viable for this model with a payback period of five (5) years for a useful life of 20 years. With the initial cost of PhP102, 820 ($2000), the annual savings will be PhP33,600 ($650) when operating the system at the maximum operation.